Marine debris from the past - Contamination of the Brazilian shore by a WWII wreck - Teixeira, Carlos Eduardo Peres (2021)
In 2018, unidentified packages appeared along approximately 1600 Km of the Brazilian coastline causing widespread pollution to beaches and danger to society. The packages were found to be bales of raw rubber ranging in size from 0.06 m3 to 3.4 m3 and weighing up to 200 kg. A few bales were marked with the stamp “Product of French Indochina” and colonized by the barnacle Lepas anatifera, an oceanic species. We found that unidentified packages are from a Second World War (WWII) shipwreck, and that the source is almost certainly the SS Rio Grande found at 5,762 m depth. Numerical simulations show that currents can carry out the bales from the SS Rio Grande to the beaches. We highlight transnational measures to study and protect the WWI shipwrecks because they represent an overlooked environmental ris